Answer:
Explanation:
in order to solve this system of equation we would say that let
3x+2y=-8........................................................ equation 1
1 x - y = -1 ........................................................ equation 2
from equation 2
1 x - y = -1 ........................................................ equation 2
x = -1 + y....................................... equation 3
substitute for equation 3 in equation 1
3x+2y=-8........................................................ equation 1
3( -1 + y) + 2y = 8
-3 + 3y +2y = 8
collect the like terms
-3 + 5y = 8
5y = 8 + 3
5y = 11
divide both sides by the coefficient of y
5y/5 = 11/5
y = 2.2
put the value y = 2.2 into equation 3
x = -1 + y....................................... equation 3
x = -1 + 2.2
x = 1.2
therefore th value of x is 1.2 and y is 2.2